Notes on the reproductive biology of Edwardsiella (Cnidaria, Actiniaria): new insights into Edwardsiella loveni - Chagas, Barbara M.T. [UNESP]; Daly, Marymegan; Waller, Rhian; Stampar, Sérgio N. [UNESP] (Taylor & Francis, 2025)
Reproductive biology remains poorly understood for many actiniarian species, as exemplified in the understudied genus of burrowing anemones Edwardsiella. To address the gaps in the literature and deepen our knowledge of the reproductive biology of Edwardsiella, we investigate the reproductive morphology of the species Edwardsiella loveni based on museum specimens. We confirm that individuals of E. loveni exhibit either oocytes or spermatocysts, indicating likely gonochorism. Gametogenesis in E. loveni appears to be synchronous across individuals. Fecundity was high, with thousands of oocytes present in the female individual. These findings emphasize the existing gap in the literature on the reproductive biology of Edwardsiella and contribute to the limited knowledge on their reproduction, providing a basis for future studies on the genus.